2008
DOI: 10.1560/ijps.56.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Local old olive landrace varieties in Israel—Valuable plant genetic resources in olive cultivation

Abstract: It is assumed that the cultivation of olive trees started in the East Mediterranean in the third millennia Bce. Throughout history and until recently, successful olive clones were maintained vegetatively and were grafted either on seedlings or on spheroblasts removed from the base of the trunk. It therefore can be hypothesized that local old olive trees, older than 500 years might represent an ancient gene pool. Modern terminology categorizes local genotypes into four main variety groups. However, in tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…‘Favarol’ is another cultivar once grown in the GT area [ 3 ], but the two trees collected under this name clustered distantly from the ‘Favarol’ group of accessions from local collections ( Figure 2 ). The fact that most of the GT genotypes could not be assigned to known cultivars is in agreement with previous reports on ancient genotypes, which suggested that traditional olives are confined in their putative domestication areas [ 67 , 68 ]. Some of them could be feral.…”
Section: Discussionsupporting
confidence: 90%
“…‘Favarol’ is another cultivar once grown in the GT area [ 3 ], but the two trees collected under this name clustered distantly from the ‘Favarol’ group of accessions from local collections ( Figure 2 ). The fact that most of the GT genotypes could not be assigned to known cultivars is in agreement with previous reports on ancient genotypes, which suggested that traditional olives are confined in their putative domestication areas [ 67 , 68 ]. Some of them could be feral.…”
Section: Discussionsupporting
confidence: 90%
“…In the 20 th Century, an inventory of 27 different olive varieties in former Palestina [ 15 ] suggests that in the long history of olive cultivation, cultivars adapted to different regions of the area were selected [ 16 ]. Today, local terminology recognizes four cultivars in traditional olive cultivation in the Levant: Souri, Nabali Baladi, Nabali Muhasan and Mallisi.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-seven other local olive cultivars were described in the first half of the 20 th century by Goor (1948). These are divided in current terminology into five main cultivars: Nabali Baladi, Nabali Muhassan, Mailsi, Souri, and Souri Rumi (Barazani et al, 2008). Local olive growers consider the latter cultivar to be a remnant of olive trees from the Roman period.…”
Section: Olive Landraces Of the Southern Levantmentioning
confidence: 99%